Epic of evolution : seven ages of the cosmos - Chaisson, Eric (Columbia University Press, 2006)
How did everything around us-the air, the land, the sea, and the stars-originate? What is the source of order, form, and structure characterizing all material things? These are just some of the grand scientific questions Eric J. Chaisson, author of the classic work Cosmic Dawn, explores in his enthralling and illuminating history of the universe. Explaining new discoveries and a range of cutting-edge ideas and theories, Chaisson provides a creative and coherent synthesis of current scientific thinking on the universe's beginnings. He takes us on a tour of the seven ages of the cosmos, from the formless era of radiation through the origins of human culture. Along the way he examines the development of the most microscopic and the most immense aspects of our universe and the complex ways in which they interact. Drawing on recent breakthroughs in astrophysics and biochemistry, Chaisson discusses the contemporary scientific view that all objects-from quarks and quasars to microbes and the human mind-are interrelated. Researchers in all the natural sciences are beginning to identify an underlying pattern penetrating the fabric of existence-a sweepingly encompassing view of the formation, structure, and function of all objects in our multitudinous universe. Moreover, as Chaisson demonstrates, by deciphering the scenario of cosmic evolution, scientists can also determine how living organisms managed to inhabit the land, generate language, and create culture. Epic of Evolution offers a stunning view of how various changes, operating across almost incomprehensible domains of space and nearly inconceivable stretches of time and through the evolutionary combination of necessity and chance, have given rise to our galaxy, our star, our planet, and ourselves.